An intercontinental expansion of European club competitions: A new reality? The case of Dubai and EuroLeague - Mendizabal Leiñena, Xabier (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Euroleague is the second-best basketball league worldwide. To grow the competition, Euroleague plans to integrate a team from Dubai. The aim of this study was to meaningfully contribute to the discussion about the feasibility of this idea. Through a case study, using an exhaustive analysis of primary and secondary sources, we analyzed the peculiar nature of Euroleague, the consequences of this expansion on European basketball and the vision of Gulf countries governments regarding sport investments. We found that Dubai fits partially the conditions for Euroleague membership. Theoretically, Euroleague could become a paradigm-changing organization. Practically, it could attract interest from leagues due to this idea. However, it could affect interdependencies with other stakeholders and attract criticism due to the human rights record in Emirates. This underscores the importance of stakeholder engagement in this initiative to create lasting social change in Dubai, promoting sport as a positive force.